Factors affecting default payment on microcredit loan case study of Amanah Ikhtiar Malaysia, Bukit Mertajam branch / Norhafize Ab Wahab and Noor Faezah Abdul Nasir - Ab Wahab, Norhafize; Abdul Nasir, Noor Faezah (Faculty of Business and Management, 2013)
Micro credit is a product of micro finance institutions. It can be defined as financial instruments such as savings, insurance, loans and other financial products that only focus to the poor. In Malaysia, one of institution that provides micro credit is Amanah Ikhtiar Malaysia (AIM). AIM or Ikhtiar was established in 1987 as a Registered Private Trust (under the Trustees Incorporation Act 1952 (Revised 1981). Our objectives of this study is to determine the factors affecting default payment on micro credit loans, to determine the relationships between the independent variables (borrower, business, lender and loan characteristics) and the dependent variables (default payment), and to determine the most significant factor affecting default payment. We used simple random sampling to select 150 respondents among borrowers that having problem to pay backs the loan. We only focus to Sungai Acheh block which is has 243 borrowers who have default case. From our study, we found that the most significant factor that affecting to default payment is borrower/individual characteristic with highest t-value among other factors which is 4.232 and also highest beta value that is 0.348. It is significant because the p-value is less than 0.05. Since borrower/individual characteristics are significant in influences default payment on micro credit loan thus the hypothesis 1 is accepted.